To simplify the expression \((4x^3)^3\) using the properties of integer exponents, we can apply the power of a product property and the power of a power property.
-
The expression can be broken down as follows: \[ (4x^3)^3 = 4^3 \cdot (x^3)^3 \]
-
Now, simplify each part: \[ 4^3 = 64 \quad \text{and} \quad (x^3)^3 = x^{3 \cdot 3} = x^9 \]
-
Multiply the results together: \[ 64 \cdot x^9 = 64x^9 \]
So, the correct simplified expression is \(64x^9\).
Therefore, the correct option is Option B: 64x^9.
Enter 2 for Option B.